Does tranexamic acid reduce blood loss during head and neck cancer surgery? - Atul P Kulkarni; Devendra A Chaukar; Vijaya P Patil; Rajendra B Metgudmath; Rohini W Hawaldar; Jigeeshu V Divatia (Indian Journal of Anaesthesia, 2016)
Background and Aims: Transfusion of blood and blood products poses several hazards. Antifibrinolytic agents are used to reduce perioperative blood loss. We decided to assess the effect of tranexamic acid (TA) on blood loss and the need for transfusion in head and neck cancer surgery. Methods: After Institutional Review Board approval, 240 patients undergoing supramajor head and neck cancer surgeries were prospectively randomised to either TA (10 mg/kg) group or placebo (P) group. After induction, the drug was infused by the anaesthesiologist, who was blinded to allocation, over 20 min. The dose was repeated every 3 h. Perioperative (up to 24 h) blood loss, need for transfusion and fluid therapy was recorded. Thromboelastography (TEG) was performed at fixed intervals in the first 100 patients. Patients were watched for post-operative complications. Results: Two hundred and nineteen records were evaluable. We found no difference in intraoperative blood loss (TA - 750 [600–1000] ml vs. P - 780 [150–2600] ml, P = 0.22). Post-operative blood loss was significantly more in the placebo group at 24 h (P - 200 [120–250] ml vs. TA - 250 [50–1050] ml, P = 0.009), but this did not result in higher number of patients needing transfusions (TA - 22/108 and P - 27/111 patients, P = 0.51). TEG revealed faster clot formation and minimal fibrinolysis. Two patients died of causes unrelated to study drug. Incidence of wound complications and deep venous thrombosis was similar. Conclusion: In head and neck cancer surgery, TA did not reduce intraoperative blood loss or need for transfusions. Perioperative TEG variables were similar. This may be attributed to pre-existing hypercoagulable state and minimal fibrinolysis in cancer patients.